2002
DOI: 10.3346/jkms.2002.17.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Donor Specific Response of Estrogen and Progesterone on Cultured Human Melanocytes

Abstract: The mechanisms of estrogen and progesterone in human cutaneous pigmentation are largely unknown. The molecular identification of estrogen receptor (ER) and progesterone receptor (PR) in the human melanocytes is of great importance to understand the mechanisms. We performed immunocytochemistry analysis and demonstrated that ER and PR were expressed in the cytoplasms and nuclei of human melanocytes. Reverse transcriptase-polymerase chain reaction (RT-PCR) and sequence analysis confirmed the expression of ER and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
(18 reference statements)
2
25
2
2
Order By: Relevance
“…It is well known that estrogen increases the pigment cell activity [14]. It was reported that human melanocytes express ESR which have specific action in human pigmentation [32,33]. However, the genetic mechanisms of estrogen in human skin pigmentation are not known largely.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that estrogen increases the pigment cell activity [14]. It was reported that human melanocytes express ESR which have specific action in human pigmentation [32,33]. However, the genetic mechanisms of estrogen in human skin pigmentation are not known largely.…”
Section: Discussionmentioning
confidence: 98%
“…Alterations in CAT have been reported to result in the reduction of the catalase enzyme activity and consequently evoke excess H 2 O 2 accumulation in the entire epidermis of vitiligo patients (Casp et al 2002). Although the genetic mechanisms of estrogen in increased pigment cell activity are not largely known yet, ESR1 expression on human melanocytes has been demonstrated to have specific actions in human pigmentation (Im et al 2002). Also, genetic variation in ESR1 gene has been reported to show its association with vitiligo (Jin et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Vitro studies. [4,5] have shown that cultured human melanocytes express oestrogen receptors and estradiol increases the levels of tyrosinase, tyrosinase-related-protein 1 and 2, the enzymes involved in human eumelanogenesis within normal human melanocytes. Although, oestrogen has been hypothesized to be central in the pathogenesis of melasma, there had been few studies to support this view.…”
Section: Discussionmentioning
confidence: 99%